Social Manifestation in India in the Islamic period - الاستاذ المساعد الدكتورة خولة شاكر محمد الدجیلي (College of Education for Women, 2019)
The Social life contain an important side from the inherited Civilization to any nation, is distinguished by activity and zeal. The old Indian is characterized with closed and solidify socilal systems. This state had its influences on the activities of the social movment. It astonished the conquered mushins - Arab to the India from the end of the first centuny A.H we tried to change it by good works and made them become aware, so this made radical active in the social India in Islamic period which is form humanbeing nobilitie and their active deal in the society.